Changes in plasma protein concentrations in ponies with experimentally induced alimentary laminitis - Fagliari, J. J.; McClenahan, D.; Evanson, O. A.; Weiss, D. J. (Amer Veterinary Medical Assoc, 1998)
Objective-To determine whether plasma protein concentrations were altered in ponies with alimentary laminitis.Animals-12 adult ponies.Procedure-Acute laminitis was induced in 6 ponies by oral administration of carbohydrate (85% corn starch, 15% wood flour); the other 6 ponies were used as controls. A physical examination was performed and blood samples were collected immediately before and 4, 8, 12, 24, and 28 hours after administration of carbohydrate. Plasma protein concentrations were determined by means of sodium dodecyl sulphate-polyacrylamide gel electrophoresis.Results-19 plasma proteins ranging from a molecular weight of 24,000 to a molecular weight of 350,000 were identified in all 12 ponies. Plasma concentrations of proteins with molecular weights of 350,000 (fibrinogen), 130,000 (ceruloplasmin), 118,000 (c-reactive protein), 67,000 (alpha(1)-antitrypsin I), 65,000 (alpha(1)-antitrypsin II), 50,000 (haptoglobulin), and 45,000 (acid glycoprotein) were significantly increased in ponies with laminitis, compared with concentrations in control ponies.Conclusion-Changes in plasma protein concentrations are detectable within 4 hours after the onset of alimentary laminitis in ponies.Clinical Relevance-Measurement of plasma protein concentrations may be useful in monitoring the progression of laminitis in ponies.